THE USE OF SOIL RENEWAL MATERIALS TO IMPROVE CHEMICAL PROPERTIES IN INCREASING THE RESULTS OF ONIONS FROM TUMBERS - Elizabet Pakpahan, Tience; Hidayatullah, Taufiq; Romulo Siagian, Deddy; Mardiana, Eva (Politeknik Negeri Lampung., 2024)
In line with the increase number of populations, the shallot demand is also increase. Thus, some efforts are needed to increase the shallot production on the degraded agricultural land, especially on ultisol. This study aimed to (1) identify the best dose of organic matter and mycorrhiza and the interactions between these two treatments in increasing shallot production on ultisol, (2) analyze the improvement of chemical properties of ultisols using mycorrhiza and organic fertilizer, and (3) measure the increase of vegetative and generatif (production) growth of shallot using these treatments. The study was designed by factorial randomized block design with some levels. Treatment 1 (Mycorrhiza), M0 = Control, M1 = 10 g/polybag, M2 = 20 g/polybag, M3 = 30 g/polybag, M4 = 40 g/polybag, and Treatment 2 (Organic Fertilizer), P0 = Control, P1 = organic fertilizer (0.6 kg/polybag), P2 = organic fertilizer (1.2 kg/polybag), P3 = organic fertilizer (1.8 kg/polybag), P4 = organic fertilizer (2.4 kg/polybag). The results show that the mycorrhiza treatment just give the significant effect on the paramters of the wet and dry shallot weights. The highest result was found in the M4 treatment (13,9 dan 1,79 gr) and the lowest in the M0 treatment (7,89 dan 0,86 gr) for the wet and dry shallot weigths respectively. The organic fertlizer gives significant effects on all parameters, for the highest output was found in the P3 (30,24 cm, 38,47 leaves, 12,75 gr dan 1,58 gr) dan the lowest from P0 (12,58 cm, 9,57 leaves, 5,46 gr dan 0,86 gr) for the parameters of the height, number of leaves, wet weight and dry weight, respectively. The interaction between two paramters did not give the significant effect on the wet and dry weights. Fortunately, the interaction of the M4P4 treatment give significant effect on the height parameter (37,17 cm) and the M1P3 treatment give significant effect on the parameter of the number of leaves (46 number of leaves).